An Enriched, Cereal-Based Bread Affects Appetite Ratings and Glycemic, Insulinemic, and Gastrointestinal Hormone Responses in Healthy Adults in a Randomized, Controlled Trial. Issue 2 (10th December 2014) - Gonzalez-Anton, Carolina; Lopez-Millan, Belen; Rico, Maria C; Sanchez-Rodriguez, Estefania; Ruiz-Lopez, Maria D; Gil, Angel; Mesa, Maria D
Abstract: Background: Bread can contribute to the regulation of appetite. Objective: The objective of this study was to investigate the appetite ratings and postprandial glucose, insulin, and gastrointestinal hormone responses related to hunger and satiety after the intake of a cereal-based bread. Methods: A randomized, controlled crossover trial was conducted in 30 healthy adults (17 men and 13 women) aged 19–32 y with body mass index of 19.2–28.5. Each volunteer consumed the cereal-based bread and the control bread 2 times, with a 1-wk wash-out period, over a total of 4 sessions. The cereal-based bread contained a variety of cereal flours (wheat, oat, and spelt) and consisted of 22% dried fruits (figs, apricots, raisins, and prunes). It was also enriched with both fiber (7% from wheat cross-linked maltodextrins and pea) and protein (10–11% from wheat gluten and hydrolyzed wheat proteins). The control bread consisted of white bread with margarine and jam to control for energy density, fat, and sugar content. We measured appetite ratings using standardized visual analogue scales and glucose, insulin, and gastrointestinal hormone responses over a postprandial time of 4 h after the ingestion of each bread. Linear mixed-effects models were used to compare the areas under the curve (AUCs) for different variables. Results: Consuming the cereal-based bread decreased prospective consumption more than consumption of the control bread (−5.3 ± 0.6 m · min and −4.4 ± 0.6 m · min, respectively; P = 0.02) and increased satiety more (6.2 ± 0.7 m · min and 5.2 ± 0.6 m · min, respectively; P = 0.04), although subsequent ad libitum energy intake 4 h later did not differ. Postprandial blood glucose, insulin, ghrelin, glucagon-like peptide 1 and gastric inhibitory polypeptide AUCs were lower after the ingestion of the cereal-based bread, whereas the pancreatic polypeptide AUC was higher than with the control bread ( P < 0.05). Conclusions: Consumption of the cereal-based bread contributed to appetite control by reducing hunger and enhancing satiety. In addition, consumption of this bread improved glycemic, insulinemic, and gastrointestinal hormone responses in healthy adults. This trial was registered at clinicaltrials.gov as NCT02090049.